On the enigmatic troglobitic scorpion Troglorhopalurus translucidus: distribution, description of adult females, life history and comments on Rhopalurus lacrau (Scorpiones: Buthidae) - Jonas Eduardo Gallão; Maria Elina Bichuette (Zoologia (Curitiba))
ABSTRACT We describe for the first time the adult female of the troglobitic scorpion Troglorhopalurus translucidus Lourenço Baptista & Giupponi, 2004, and broaden its known distribution to other sandstone caves at Chapada Diamantina's region. The life history of T. translucidus is reconstructed through morphometric measurements, with a multivariate analysis applied on a set of 16 specimens in all stages (including the holotype) and biological notes. The ontogeny of T. translucidus has seven stages and the litter size is 43 (n = 1). We discuss the isolation of T. translucidus and Rhopalurus lacrau Lourenço & Pinto-da-Rocha, 1997 in caves of Chapada Diamantina, and discuss their troglomorphisms (autapomorphies) among other species related with Rhopalurus . Both species must be considered fragile due their restricted endemism at Chapada Diamantina.